Analyses of a few physiological parameters of hybrid wheat in the case of different nitrogen supply levels - Kiss, László; Zsombik, László; Veres, Szilvia (Acta Agraria Debreceniensis, 2016)
The winter wheat is one of the most determinant crops because its role was always important in human’s life. To increase the average yield there are several possibilities, which are still not clear fields of agricultural plant production. Our main goal was to examine the responses of winter wheat genotypes to different amounts of nitrogen supplies. The sowing area of hybrid wheats are increasing, they may have different nutrient nitrogen utilization compared to varieties, and the question arose if it is possible to achieve same yield at lower nitrogen fertilizer application or not. The present study analyzes the results of winter wheat (Triticum aestivum L.) from tillering growing stage. Under controlled conditions three different wheat hybrids were grown (Hywin, Hystar, Hybiza) with two different amounts of nitrogen supplies (optimal and the fourth part). The dry matter accumulation, relative chlorophyll content and nitrogen content were measured in order to draw conclusions from the different supplies of nitrogen for winter wheat genotypes and their physiological plasticity.